PROSPECTIVE DIRECTIONS OF CIVIL SOCIETY IN UZBEKISTAN - Akmal Abdullaev (International Scientific and Current Research Conferences, 2021)
The article reveals the prospects for the development of civil society in Uzbekistan and analyzes the problems of the development of legal consciousness and legal values in modern society, identifies important structural and material differences between law and law, which is one of the main components of law.